Welfare Effects of Emission Taxes in Norway - Jørgen Aasness; Torstein Bye; Hans Terje Mysen (Statistics Norway, Research Department, 1995)
The welfare effects of introducing taxes on emissions of carbon dioxide is analysed within an empirical general equilibrium model of the Norwegian economy. A CO2 tax regime where we aim at stabilising the CO2 emissions at the 1990 emission level in 2020 is compared to a reference scenario without such taxes. In the simulations introduction of CO2 taxes reduces gross domestic product, but increases net national real disposable income, private consumption and money metric utility. This difference in sign is due to a positive terms of trade effect, some of the CO2 taxes will be paid by foreigners through exports. The welfare effects differ from household to household depending on the composition of their total consumption. Poor households are less favourably affected than rich households, due to smaller budget shares for the rich households on consumer goods which imply relatively much CO2 emissions.
Keywords: E1; H3; I3; Q4; 330; CO2 taxes; general equilibrium model; money metric welfare; terms of trade